INTEGRATING GENRE SKILLS AND READING SKILLS IN TEACHING READING TO INCREASE STUDENTS’ COMPREHENSION IN EFL CLASSES - Jufri Syahrudin (Universitas Negeri Padang, 2013)
This paper is aimed at discussing the way how to integrate genre skills and reading skills in teaching reading at EFL classes in Indonesia. These two skills should be taught simultaneously in the classroom by the teacher as genre-based approach is applied in teaching reading today at junior and senior high schools. By this approach, the students are expected to be able to comprehend some kinds of monologue texts, such as narrative, recount, descriptive, procedure, explanation and exposition and functional texts like advertisement, announcement, letter, invitation and so forth. On the other hand, the students are also demanded to acquire the reading sub-skills in order that they are able to comprehend the text well. These reading sub-skills are unavoidable to get by the students because they will help them to read more effectively, quickly and easily. For this reason, a reading teacher should be able to find the way how to integrate the genre skills and reading skills in reading classes. If the teacher cannot do that, he/she will fail in his/her job. In this paper, the writer will discuss more deeply about this issue, so that the reader, especially teachers later on will get more information and knowledge in teaching reading. To do the integration, the teacher does not only need appropriate teaching techniques, but also media and materials chosen. In addition, how the teacher designs teaching and learning activities will determine the success in the classroom.